Future research agenda for FM in the Nordic countries in Europe. Issue 1 (2014) - ,; ,; ,
Abstract : Purpose – The purpose of this paper is to identify trends and challenges in relation to the FM profession in the Nordic countries of Europe and to identify inputs to a common Nordic research agenda.Design/methodology/approach – The study is based on theory from innovation systems and strategic foresight. First, a review of literature was carried out and an innovation systems model of the FM sector was developed. Second, four national workshops were held involving FM practitioners and researchers from Denmark, Norway, Sweden and Finland. Third, the results of the workshops were presented and discussed at a Nordic FM conference in August 2011. Finally, an adapted Delphi survey was carried out as a final data collection and validation of the findings. This article has the main focus on the results of the Delphi survey.Findings – The results of the study show that the main issues vary considerably between the four countries, both with regards to megatrends in the strategic environments, the current trends and challenges and the future needs for new competences and knowledge. Despite the large national differences the study is able to identify joint interest across the four countries. Based on the study a common Nordic research agenda is proposed with two headlines: Valuation and professionalization of FM, and Resources and sustainability.Research limitations/implications – The study provides directions for future research with particular focus on the Nordic countries in Europe.Practical implications – The study identifies trends and challenges as well as need for new knowledge and competences for FM practice in each of the four Nordic countries.Originality/value – This is the first comprehensive foresight study aimed at developing a research agenda for FM across the Nordic countries.